Clinical supervision in nursing – strategy for knowledge and quality of care - Carvalho, António Luís (2017)
The demands placed on health professionals, mainly on nurses, are varied and highly complex. We live with changes in lifestyles, an increase in chronic diseases and an increasingly advanced age, raising the need to monetize resources and guarantee excellence of care. These factors, among many others, impel health professionals to think about their practice and develop strategies that ensure their personal and professional development. The increasing complexity of health problems has highlighted the interest in understanding the implications of the concepts of multidisciplinarity, interdisciplinarity and transdisciplinarity in care, thereby resulting in the need to ensure strategies for developing the knowledge and the discipline of nursing.